Assessing the Environmental Impact of Bubble Wrap: A Life Cycle Assessment using LCA FE Software - Muhammad Khalis Fathris Mohd Khairi; Tengku Nur Azila Raja Mamat; Yong Tze Me; Shaiful Rizal Masrol; Emelia Sari (Journal of Advanced Industrial Technology and Application, 2025)
Packaging plays a key role in protecting goods, especially in e-commerce and logistics, where bubble wraps are valued for their lightweight and durable nature. However, its widespread use raises environmental concerns, including resource depletion and waste. This study explores the sustainability of remanufacturing secondary packaging, specifically bubble wrap, using a Life Cycle Assessment (LCA) approach via LCA for Experts (LCA FE) software. The assessment covers the full life cycle of single-layer LLDPE bubble wrap—from raw material extraction and manufacturing (extrusion, bubble formation, cooling, cutting) to end-of-life disposal. The LCA tracks energy use, materials, and environmental impacts to identify hotspots. Results show fossil resource depletion (ADP Fossil) is the dominant impact, accounting for 95.47%, mainly due to LLDPE production. Other notable impacts include global warming potential and freshwater aquatic ecotoxicity, largely driven by manufacturing energy use, while transport and disposal have minor effects. The study highlights the need for more sustainable packaging through biodegradable materials, better recycling, and circular economy principles to reduce environmental impact.